2014
DOI: 10.1155/2014/157102
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Multi-Drug Resistant Organisms in a Teaching Hospital in Oman: A One-Year Hospital-Based Study

Abstract: Background. Antimicrobial resistance is increasingly recognized as a global challenge. A few studies have emerged on epidemiology of multidrug resistant organisms in tertiary care settings in the Arabian Gulf. Aim. To describe the epidemiology of multi-drug resistant organisms (MDRO) at Sultan Qaboos University Hospital, a tertiary hospital in Oman. Methods. A retrospective review of MDRO records has been conducted throughout the period from January 2012 till December 2012. Organisms were identified and tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 28 publications
6
40
0
2
Order By: Relevance
“…There are limited published data on antimicrobial resistance in Oman. A study by Balkhair et al found that multidrug resistance among clinical isolates of A. baumannii, P. aeruginosa, and Enterobacteriaceae was prevalent in hospitalized patients (Balkhair et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There are limited published data on antimicrobial resistance in Oman. A study by Balkhair et al found that multidrug resistance among clinical isolates of A. baumannii, P. aeruginosa, and Enterobacteriaceae was prevalent in hospitalized patients (Balkhair et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Despite distinctive improvements in healthcare delivery in emerging economies, recent reports suggest that the progress might be hindered by existing sub-optimal safety measures essential for best practice in delivering healthcare [ 1 ]. In response to this trend, the World Health Assembly ‘Resolution 55.18’ in 2004 proposed to set-up mechanisms to increase what was termed ‘life-saving patient safety solutions’ [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Physicians represented about 46% of the participants who responded to all questionnaire questions. Demographic data of participants were shown in Table [1]. Participants' ages ranged from 23-56 years with average ages of 41 ± 8.9 years.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the great advance in healthcare delivery in emerging economies, hazards related to health care are still in focus with international reports showing their dangers [1,2]. Preventable medical errors were reported to cause 44000-99000 deaths annually [3].…”
Section: Introductionmentioning
confidence: 99%